Knowledge, practices and respiratory symptoms among selected factory workers in regards to dust exposure - Ruslan, Nur Afiqah (Universiti Sains Malaysia, 2015)
Cement Industries of Malaysia Berhad (CIMA Group) has been involved in the manufacturing and distribution of cement and related activities. Regardless of the cement manufacturing, dust is the major industrial pollutant towards the workplace environment. Dust is emitted throughout all these processes especially during the transferring processes and the crushing processes. This study was conducted to determine the association between knowledge, practices and respiratory symptoms among workers in cement industry. A cross sectional study was conducted, recruiting 56 cements workers at the final processing section at Negeri Sembilan Cement Industry (NSCI). A walk through checklist and questionnaire were applied for data collection and data was analysed using SPSS version 22. The workers that stationed at final processing area were exposed to the dusty environment at high risk rating. Majority of the workers never worked at dusty workplace other than NSCI (71.4%, n=40). Most of the workers preferred to used dust mask at the workplace (80.4%, n=45). Half of the workers coughed with sputum (50%, n=28). There was a significant association between knowledge that respiratory protector can prevent from respiratory problem with the frequency of wearing respiratory protector at the workplace (p=0.001). The association between the knowledge regarding to wellfunctioned of dust control system with respiratory symptoms such as coughing early in the morning and cough with sputum showed significant association with (/?<0.05). There was an association on respirator wearing with the respiratory symptoms among the workers (p<0.05). As a conclusion, there is quite an average association between knowledge on dust exposure, practices in wearing respiratory protector and respiratory symptoms among the workers at NSCI. Implementation of sufficient measures should be the first step to improve health and safety performance in the cement industry.